2004
DOI: 10.1638/02-056
|View full text |Cite
|
Sign up to set email alerts
|

Electrocardiography of Rock Partridges (Alectoris Graeca) and Chukar Partridges (Alectoris Chukar)

Abstract: Standard limb, six lead (I, II, III, aVR, aVL, and aVF) electrocardiograms (ECGs) were recorded in 10 awake mature rock partridges (Alectoris graeca) and 10 chukar partridges (Alectoris chukar). Durations and amplitudes of P and T waves and QRS complexes, durations of P-Q and Q-T intervals, and mean heart rates were calculated from the lead II ECGs. All observable P and T waves were negative in aVR and aVL, whereas they were positive in all remaining leads. The most frequent forms of QRS complex were r-s (r-S)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
8
2
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 8 publications
9
8
2
1
Order By: Relevance
“…The P waves were dominantly positive in all leads except for lead aVR and only in male pheasants it was biphasic in lead aVL. In this respect, there is compatibility between our results and those findings reported by many authors [16,17,[28][29][30] . On the other hand, Hassanpour et al found that the P waves were mainly positive in all leads in green peafowl [31] and in helmeted guinea fowl [32] .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The P waves were dominantly positive in all leads except for lead aVR and only in male pheasants it was biphasic in lead aVL. In this respect, there is compatibility between our results and those findings reported by many authors [16,17,[28][29][30] . On the other hand, Hassanpour et al found that the P waves were mainly positive in all leads in green peafowl [31] and in helmeted guinea fowl [32] .…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, in lead aVR and aVL the most frequent morphologies were qR. Our findings were almost similar to results obtained in many studies [15][16][17]28,[30][31][32] .…”
Section: Tablo 2 Dişi Ve Erkek Sülünlerde P Qrs Ve T Dalgalarına Aisupporting
confidence: 92%
See 3 more Smart Citations